(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
The Central Java Catholic community, inaugurated as Vicariate Apostolic of Semarang on June 25, 1940 had already 21 parishes. This year (2025) it celebrates its 85th anniversary and has developed into a modern religious organization managing more than 100 parishes, enjoy ing an almost 500% increase in the number of parishes. Unlike other Dioceses in Indonesia, the Semarang community has been led by an indigenous Bishop since its inception. This fact certainly had provided an "Indonesian flavor" to the management of the local hierarchy since the beginning. Its first Bishop, Monsigneur Soegijapranata is a futuristic leader. As the founding father, he plays crucial role in putting foundation for the development of this organization. This article focuses on the vision statement of the Bishop and argues that the concept of ’masjarakat katolik’ he mentioned in his vision is ’the Catholic society’ and best represented by Parish.